PENGARUH MODEL PEMBELAJARAN SCRAMBLE BERBANTUAN FLASHCARD TERHADAP HASIL BELAJAR MATERI KLASIFIKASI MAKHLUK HIDUP - Rabeka, Rabeka; Yeni, Laili Fitri; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of flashcard-assisted flash driven scramble model on student learning outcomes on classification material of VII class of SMP Negeri 3 Sungai Raya. This form of research is true experimental design with posttest-only control design. The research sample is class VII H as experimental class and VII G as control class, with intact group sampling technique. Instruments used multiple choice test amounted to 20 questions. The average of the students' learning outcomes in the experimental class is 17.33, while in the control class is 16.1. The result of t test analysis obtained tcount> ttable is 37.235 > 9.210, meaning there is a significant difference between the learning outcomes of students who were taught using flashcard-assisted flash driven scramble model with those taught using conventional learning model. The effect size is 0.97 with high category, giving 33.40% influence.Keywords: Scramble model, Flashcard, learning outcomes, material        classification of living creatures